Tomographic osteometry of the zygomatic bone applied to traumatology of facial bones: Preliminary retrospective study of zygomatic summit in 28 patients. Issue 1 (January 2017) - Lerhe, Barbara; Alshehri, Sarah; Ferachon, Denis; Dejean, Sébastien; Salabert, Anne Sophie; Lopez, Raphael
Abstract: Background: The available referential measures defining the zygomatic bone morphology are adequate enough for full determination of the zygoma positioning, especially for trauma surgery, but osteometric analysis of the zygoma positioning based on tomographic examinations could be useful in peroperative and postoperative imaging. In this study, we propose referential measures, taking into account the morphology and the symmetry of the zygoma. In addition, the reliability and reproducibility are considered. Methods: Thirty normal computed tomography (CT) scans were used to establish the referential measures. The study involved preoperative imaging (27 CT and 1 cone beam CT [CBCT] scan), and postoperative imaging (6 CT and 22 CBCT scans) pertaining to 28 patients, showing a unilateral zygomatic fracture. In a precisely chosen axial cut in the orbito-meatal plane, 3 referential data were defined: namely, S, denoting the distance of the zygoma summit; αS, representing the angle between the summit and the symmetry axis passing through the clivus; and αZ, corresponding to the morphologic angle. Results: The 3 referential measures S, αS, and αZ are reliable and reproducible by CT and CBCT examination. Those parameters can be used to evaluate the zygomatic symmetry. The postoperative asymmetries arise from an erroneous recovery of S, which was statistically significant at p  = 0.0216. Conclusion: On a single optimized axial cut, the new referential measures are useful and effective in preoperative and postoperative assessment of the residual bone asymmetries. Clinical question/Level of evidence: Therapeutic, III.